Neutrophils in Tuberculosis: Heterogeneity Shapes the Way? - Irina V. Lyadova (Mediators of Inflammation)
Infection with M. tuberculosis remains one of the most common infections in the world. The outcome of the infection depends on host ability to mount effective protection and balance inflammatory responses. Neutrophils are innate immune cells implicated in both processes. Accordingly, during M. tuberculosis infection, they play a dual role. Particularly, they contribute to the generation of effector T cells, participate in the formation of granuloma, and are directly involved in tissue necrosis, destruction, and infection dissemination. Neutrophils have a high bactericidal potential. However, data on their ability to eliminate M. tuberculosis are controversial, and the results of neutrophil depletion experiments are not uniform. Thus, the overall roles of neutrophils during M. tuberculosis infection and factors that determine these roles are not fully understood. This review analyzes data on neutrophil defensive and pathological functions during tuberculosis and considers hypotheses explaining the dualism of neutrophils during M. tuberculosis infection and tuberculosis disease.